EFFECTS OF DYEING CONDITIONS ON THE COLOR AND COLORFASTNESS OF COTTON YARN DYED WITH THE MUD FROM CHAIYAPHUM PROVINCE - Wewa, Suthawadee; Phiromthamsiri, Kajijarus; Kraisuwan, Suteeluk (Srinakharinwirot University Journal of Sciences and Technology, 2023)
This research aimed to study effects of dyeing conditions on the color and colorfastness of cotton yarn dyed with the mud from Ban Nong Hoi, Nong Bua Daeng Subdistrict, Nong Bua Daeng District, Chaiyaphum Province. For dyeing experiments 100 200 and 300 grams of mud per liter of water were used. Two methods of mud solution preparation were used 1) dissolving the mud and left for 1 hour before dyeing and 2) dissolving the mud and then immediately used for dyeing. After dyeing, the color values were measured and the tests for color fastness to washing, to light and to abrasion were performed. The results of the study found that, after dyeing cotton yarn with mud, the color values obtained were L* 66.81-70.31, a* 4.57-5.04, b* 16.55-17.72, C* 17.20-18.42 and h* 74.13-75.05. All dyeing methods yielded the L* a* b* and C* values with no statistical different at .05. Only in the case of h* value which was found that if 100 grams of mud per liter of water were used, the method of dissolving the mud and dyeing immediately statistically at .05 yielded a higher h* value than the method of dissolving the mud and left for 1 hour before dying. The colorfastnesses to washing, considered by the dE* of color change, were at grade 2 (poor) to grade 4 (good). It was found that if 300 grams of the mud per liter of water were used, the method of dissolving the mud and left for 1 hour before dyeing yielded a higher grade of colorfastness than the method of dissolving the mud and then dying immediately. The colorfastnesses to washing, considered by the dE* of color staining, were at grade 3 (fair) to grade 4 (good). All methods significantly had no difference at .05 level. The colorfastnesses to light were at grade 4 (good) to grade 5 (excellent). All methods significantly had no difference at .05 level. The colorfastnesses to dry abrasion, considered by the dE* of color change, were at grade 4 (good) to grade 5 (excellent). All methods significantly had no difference at .05 level. Considering the dE* of color staining the colorfastnesses were at grade 3 (fair) to grade 4 (good). All methods significantly had no difference at .05 level. The colorfastnesses to wet abrasion, considered by the dE* of color change, were at grade 4 (good) to grade 5 (excellent). All methods significantly had no difference at .05 level. And considering the dE* of color staining, the colorfastnesses were at grade 3 (fair) to grade 4 (good). All methods significantly had no difference at .05 level. The results of the study pointed out that the optimum condition for dyeing cotton yarn with the mud from Chaiyaphum province was using 100 grams of mud per liter of water by dissolving the mud and dyeing immediately.